2011
DOI: 10.1177/0883911511400251
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Bombyx mori silk fibroin/sericin films by crosslinking with PEG-DE 600 and genipin

Abstract: Silk fibroin and sericin have been widely used as a biomaterial for many different purposes. In this study, the properties of crosslinked fibroin/sericin 90/10 films have been investigated using two different crosslinkers poly(ethylene glycol) diglycidyl ether 600 (PEG-DE) and genipin. The films were characterized by molecular weight, fibroin conformation, crystallinity, and thermal stability. Both PEG-DE and genipin cross-linkers stabilized the random/α-helix structures in the fibroin and prevented phase sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 43 publications
4
49
0
Order By: Relevance
“…6 C, this behavior was due to b-sheet structure. 42,43 In addition, BSF/TSF blend lms appeared two endothermic peaks at 278. 6 C and 360.6 C, which belonged to endothermic peaks of BSF and TSF, respectively.…”
Section: View Article Onlinementioning
confidence: 99%
“…6 C, this behavior was due to b-sheet structure. 42,43 In addition, BSF/TSF blend lms appeared two endothermic peaks at 278. 6 C and 360.6 C, which belonged to endothermic peaks of BSF and TSF, respectively.…”
Section: View Article Onlinementioning
confidence: 99%
“…Addition of the isocyanate compounds to sericin films exhibits lower solubility and also lower swell ratio to the distilled water, indicating that sericin films could retain more biodegradability. Crosslinked fibroin/sericin 90/10 films fabricated using two different crosslinkers poly(ethylene glycol) diglycidyl ether 600 (PEG-DE) and genipin, exhibit good biocompatibility and support cell adhesion and proliferation [47]. Teramoto et al showed that the sericin gel film rapidly absorbs water and equilibrates at a content of about 80% without cytotoxicity [15].…”
Section: (B) Filmsmentioning
confidence: 99%
“…Motta et al [24] used PEG-DE to cross-link fibroin and sericin and indicated that PEG-DE stabilized the random/α-helix structures in the fi broin and prevented phase separation between fi broin and sericin, and the cross-linked fi lms exhibited good biocompatibility. Antheraea pernyi silk fibroin was reported to have no changes in molecular conformations caused by PEG-DE in the regenerated film at 40 ℃, and the crosslinked regenerated film showed remarkable compliance and tenacity [26] .…”
Section: Introductionmentioning
confidence: 98%
“…The molecular conformation of regenerated SF material can be translated from random coil structures into β-sheets (Silk II) or β-turns induced by genipin, to obtain water-insoluble SF materials [23] . The genipin crosslinked silk fi lm displayed highest elongation at break and tensile strength [24] . In addition, metal ions such as cupric ion can induce the SF secondary structure transition from an amorphous to a β-sheet structure [25] .…”
Section: Introductionmentioning
confidence: 99%